2017
DOI: 10.5539/ijbm.v12n2p171
|View full text |Cite
|
Sign up to set email alerts
|

Are Countries Participating into Regional Integration Performing Better in Growth and Liberalization Than Non-Participators? A Study on European Countries

Abstract: This study conducted towards identifying practical scenario of effectiveness of regional integration on indicators of trade liberalization and economic growth. Empirical analysis using secondary yet quantitative data using eight ratio and trend analysis on 49 European countries (28 EU and 21 Non-EU) portrays outcome in favor of regional integration. While EU countries seem to be performing consistently in both the categories, Non-EU countries are lagging behind. This outcome comes in the support of the traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Vanhoudt (1999) examined the effect of regional integration and European Union (EU) membership on economic growth in a panel of 23 OECD countries and found no evidence of significant growth associated with regional economic integration. On the contrary, other authors have found a positive and significant relationship between economic integration and economic growth in Europe (Henrekson et al, 1997;Crespo-Cuaresma et al, 2017;Bose and Bristy, 2017), South Asia (Sadiq and Ghani, 2007;Rahman et al, 2012) and Southeast Asia (Bong and Premaratne, 2018). Over the years, several attempts have been made to replicate the Asian success stories of regional economic integration in other parts of the world, particularly in Africa.…”
Section: Economic Growth In Sadcmentioning
confidence: 99%
“…Vanhoudt (1999) examined the effect of regional integration and European Union (EU) membership on economic growth in a panel of 23 OECD countries and found no evidence of significant growth associated with regional economic integration. On the contrary, other authors have found a positive and significant relationship between economic integration and economic growth in Europe (Henrekson et al, 1997;Crespo-Cuaresma et al, 2017;Bose and Bristy, 2017), South Asia (Sadiq and Ghani, 2007;Rahman et al, 2012) and Southeast Asia (Bong and Premaratne, 2018). Over the years, several attempts have been made to replicate the Asian success stories of regional economic integration in other parts of the world, particularly in Africa.…”
Section: Economic Growth In Sadcmentioning
confidence: 99%
“…As a result, one critical issue is that an economic union may face some economic and institutional challenges that will impede its operations and effectiveness. Some of these challenges include productivity disparities and rising trade deficits, fiscal and financial union incompatibility (Bose, Bristy 2017), and the common central bank's limited power. The recent evolution of international relations indicates the necessity for a review of REI.…”
Section: Introductionmentioning
confidence: 99%